The Use of Probiotics in Respiratory Allergy - Gemma Vilà-Nadal,; Elsa Phillips-Anglés ,; Javier Domínguez-Ortega, (Journal of Pharmacy and Nutrition Sciences, 2016)
There is a high and steadily increasing prevalence of respiratory allergy throughout the world, especially in paediatric population and in industrialized and developing countries. A complex interplay between genetic and environmental factors has been implicated to explain this dramatic increase in prevalence of allergic diseases. It has been suggested that exposure to microbes plays a critical role in the development of the early immune system and may contribute to allergic diseases through their effect on mucosal immunity. Probiotics, microorganisms exerting beneficial effects on the host, are used in a great number of paediatric and adult diseases, mainly gastrointestinal disorders, but they have been proposed to be beneficial also in allergic diseases. Different trials have been published finding benefits in the use of probiotics in prevention and treatment of atopic dermatitis, but to date, studies have yielded inconsistent findings to support a protective association between their use on prevention of allergic rhinitis or asthma. However, probiotics may be beneficial in improving symptoms and quality of life in patients with allergic rhinitis although it remains limited due to study heterogeneity and variable outcome measures. As a result of these controversies, future investigations with a better standardization are needed. In this review, we summarize recent clinical research to elucidate the mechanisms of probiotics and their effect in respiratory allergy. According to published data, probiotics could emerge as a novel, complementary treatment option for allergic rhinitis but not for asthma.